Pertinencia de contenidos de Bachillerato General Unificado en primer nivel de carrera electrónica, automatización y control, Universidad Fuerzas Armadas, periodo Abril - Agosto 2021. - Oyagata, Lucila (2022)
The present investigation is carried out with the objective of describing the relevance of the contents of the curricular mesh of the Unified General Baccalaureate (BGU) in the permanence or repetition in the students of the first level of the Electronics, Automation, and Control career of the University of Armed Forces, in the April-August 2021 period, to demonstrate the relationship between the BGU and the Career. According to the findings of this research, it is evident that, despite there being a relationship between some subjects and their contents in comparison between curricula, firstsemester students have difficulties or gaps in knowledge, in addition to indicating that in high school they do not delve into the important content that is seen in the race. The BGU, despite having been created for articulation with higher education, does not fulfill this stated purpose. It is essential that Information and Communication Technologies (I.C.T.) be integrated into the Baccalaureate, given that the subjects taught online require adequate management of technology and programs for the execution of educational activities of the career. Another of the consequences that affected education was the COVID-19 pandemic and the virtual modality, since not all the population had internet or high-end devices, added to this the lack of knowledge of the management of programs for teaching-learnig, time was lost until getting used to virtuality, for which it was also one of the factors due to the lack of knowledge.